A Study on the Legitimization Strategy in War Discourse : ——Taking the American Speech in the Iraq War as an Example - Li, Xinyue; Li, Dekun; Sun, Guang (Pacific International Journal, 2024)
All kinds of human social activities are inseparable from language, and war is no exception. Compared with other social behaviors, people naturally have a fear and resistance to war, especially the unjust war of aggression. Faced with this situation, politicians skillfully used various discourse legitimization strategies to win public opinion support for the smooth progress of the war. This paper uses Reyes’s discourse legitimization strategy framework to analyze the discourse of American officials in the Iraq War, and reveals how the United States beautifies an aggressive war into a just and noble war against terrorism.